2000
DOI: 10.1149/1.1393246
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Neptunium in LiCl-KCl Eutectic/Liquid Bismuth Systems

Abstract: Np (kcal/g atom) ϭ Ϫ32.5 (Ϯ0.7) ϩ 0.0072 (Ϯ0.0010) T. The values of the solubility and excess partial free energy for neptunium were closer to those for plutonium rather than uranium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The rest of rare earth and all of alkali and alkaline earth accumulate in the melt in the form of chlorides and are removed from the melt at the waste salt treatment step [4]. Due to the more positive dissolution potential of Zr compared to actinides [5][6][7][8][9][10], Zr remains in the anode basket together with the noble metal fission products as long as the anodic potential is kept below the Zr dissolution potential. On the other hand, when a higher dissolution rate of actinides is required, Zr is anodically dissolved and is recovered on the solid cathode as U-Zr alloy and/or is deposited on the wall of the electrorefiner [11].…”
Section: Introductionmentioning
confidence: 99%
“…The rest of rare earth and all of alkali and alkaline earth accumulate in the melt in the form of chlorides and are removed from the melt at the waste salt treatment step [4]. Due to the more positive dissolution potential of Zr compared to actinides [5][6][7][8][9][10], Zr remains in the anode basket together with the noble metal fission products as long as the anodic potential is kept below the Zr dissolution potential. On the other hand, when a higher dissolution rate of actinides is required, Zr is anodically dissolved and is recovered on the solid cathode as U-Zr alloy and/or is deposited on the wall of the electrorefiner [11].…”
Section: Introductionmentioning
confidence: 99%
“…The standard potential of Zr 4+ /Zr is reported to be more positive than those of actinides such as U 3+ /U, Pu 3+ /Pu, Np 3+ /Np and Am 2+ /Am in LiCl-KCl melts [3][4][5][6][7]. This means that zirconium theoretically remains in the anode basket with noble metal fission products and the cladding during electrolysis as far as anodic potential is kept more negative than the dissolution potential of zirconium.…”
Section: Introductionmentioning
confidence: 99%
“…1 Assessment of feasibility of these processes requires a good knowledge of molten salt chemistry of these compounds, [2][3][4] and, therefore, basic data of these elements in molten chloride salts need to be obtained. It has been shown that the electrochemical techniques provide an efficient tool to investigate the reaction mechanisms in molten salts.…”
mentioning
confidence: 99%